Clinical waste management practices in private clinics in Selangor, Malaysia - Khanehzaei, Golyasamin (2017)
Most research findings on clinical waste in developing countries acknowledge that even though good policies and regulations exist, the clinical waste is a threat to public health and the environment due to the lack of knowledge and awareness, budget constraints, and lack of enforcement. A study on clinical waste management (CWM) was conducted among private clinics in Selangor, Malaysia to assess current management practices, the legal approach and enforcement and factors in relation to sustainability. There were 295 private clinics that participated in the questionnaire survey, from which, 57.6% were medical clinics and 42.4% were dental clinics. Semi-structured interviews and observations were also carried out among 3 medical clinics, 3 dental clinics and 6 clinical waste management organisations. A pairwise comparison survey was also conducted among clinical waste experts from related organizations. The data from the questionnaires were tabulated and analysed using descriptive statistics, cross-tab, Kruskal Wallis test, Mann-Whitney U test and factor analysis. The qualitative data from the semi-structured interviews were analysed in terms of the transcription and theme formation. Observations were also made to further address the issue of CWM. An analytic hierarchy process (AHP) was utilised to analyse expert opinions using the pairwise comparison survey.